Investigating the Effect of Increasing Slump on Compressive Strength of Nominal Mix Concrete. - Aturinda, Shallot (Kabale University, 2024)
This experimental study examined the impact of increasing slump on the compressive strength of nominal mix concrete. The research aimed to investigate the relationship between slump and compressive strength, addressing the problem of inconsistent concrete quality in construction projects. The justification for this study lies in the critical role of concrete in construction, the variability of slump in concrete mixing, and the need for optimal compressive strength. Methodologies employed in this research included preparing concrete specimens with three different mix ratios (1:2:4, 1:1.5:3, and 1:3:6) and varying slump ranges 50-75, 75-100, and 100-150. A total of 36 specimens were tested for compressive strength at 3, 7, 14, and 28 days, and the results were analyzed using statistical methods( excel software). The results showed that increasing slump led to a significant reduction in compressive strength, with the highest strength (20.1, 15.7, and 9.9MPa) observed at the lowest slump value (50, 56, and 67mm) for nominal mix ratios, 1:1.5:3, 1:2:4 and 1:3:6 respectively. The 1:2:4 mix ratio exhibited the highest compressive strength at all slump values, while the 1:1.5:3 mix ratio showed the most significant strength reduction with increasing slump. Specifically, the results revealed: a 15.8% and 59.6% reduction in compressive strength at 3 days and a 12.7% and 57.9%reduction at 28 days at respective 10% and 20% increase in water for 1:2:4 mix ratio as slump increased from 56mm to 147mm. 32.1% and 61.5% reduction in compressive strength at 3 days and a 14.4% and 63.2% reduction at 28 days at respective 10% and 20% increase in water for the 1:1.5:3 mix ratio as slump increased from 50mm to 137mm. 42.5% and 50% reduction in compressive strength at 3 days and a 9.1% and 24.2% reduction at 28 days at respective 10% and 20% increase in water for the 1:3:6 mix ratio as slump increased from 67mm to 147mm. The study's findings suggest that controlling slump within optimal ranges is crucial to achieving the desired compressive strength in concrete. Additionally, the results highlight the importance of mix ratio selection in conjunction with slump control to ensure optimal concrete performance. This research contributes to the existing body of knowledge by providing quantitative evidence of the slump compressive strength relationship. The results have practical implications for concrete producers, contractors, and engineers seeking to optimize concrete performance and inform mix design and quality control practices in the construction industry.